Peningkatan Kognitif Siswa pada Materi Dzikir dan Doa Melalui PjBL di MTsN 1 Pangandaran - Zaenudin, Ruslan (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2024)
This study aims to determine the increase in students' cognitive abilities on the material of dhikr and prayer in class VII.E MTsN 1 Pangandaran through the implementation of PjBL, to find out the application of PjBL to the material of dhikr and prayer in class VII.E MTsN 1 Pangandaran in improving students' cognitive abilities. Research result; there has been an increase in students' cognitive abilities through the use of the PjBL learning model in class VII-E at MTsN 1 Pangandaran. Judging from the pre test with completeness reached 69.23%. Post test results in the first cycle with 76.92% completeness. Post test in the second cycle of completeness obtained 100%. Through the PjBL model the results of observations on student activity in the first cycle obtained a score of 68.75%, in the second cycle it rose to 88.16%. The results of observations of groups in PBM in the first cycle averaged a score of 65.63%, in the second cycle an average score of 92.71%. The results of observations on the teacher's ability in the first cycle obtained a score of 27 or 61.36%, then in the second cycle the score increased to 40 or 90.90% of the ideal score of 44. Teachers should be able to arrange learning modules with the right steps, students are expected to more active, and the madrasah head should provide sufficient facilities for learning.